The Application of Simple Accounting Format In Tradisional Shop - Dedeh, Dedeh; Akbar, Dendy Syaiful; Putra, Rizka Andhika (Universitas Indraprasta PGRI, 2019)
This study offers to determine the ability of 20 types of MSMEs to trade in the environment around the Universitas Galuh Ciamis campus. The research method used was an experimental method, in which we applied a simple accounting format to their business. The analysis technique used is a different test (t-test) through scores obtained from test results to them before and subsequently applied to a simple accounting format. The results obtained show their low skills in preparing financial statements, as evidenced by the tests before applying a simple accounting format obtained an average score of 27.80. After applying the accounting format, improvements are made to those who prepare financial statements using a simple accounting format. From the test results applied a simple accounting format, obtained an average score of 71.20. So it can be concluded from the changes that occur before and after applying a simple accounting format for MSMEs in the type of business in the environment around the Universitas Galuh Ciamis campus.